2005
DOI: 10.1111/j.1466-7657.2004.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

A holistic approach to the promotion of older hospital patients’ health

Abstract: It was difficult to find a clear focus on health promotion. The most visible focus was on diagnosis and treatment, while the more complex and comprehensive situations related to health promotion of older patients seemed to be underprioritized. The phenomenon of 'waiting' may be an important issue for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 14 publications
5
34
0
Order By: Relevance
“…This result is important as it shows that nurses can be effective in increasing individuals' motivations and enabling older adults to pursue healthy lifestyle behaviors by having a continuous interaction with them. Studies related to this issue have found that health protection and promotion in older adults are restricted by models and approaches of care (Berg et al, 2005;Resnick, 2003a), inefficiencies in procedures and processes (Resnick, 2003a), inadequate numbers of staff (Toofany, 2008), and nurses who are considering care and services only from the medical perspective (Berg et al, 2005). The results of the current study are consistent with the literature.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is important as it shows that nurses can be effective in increasing individuals' motivations and enabling older adults to pursue healthy lifestyle behaviors by having a continuous interaction with them. Studies related to this issue have found that health protection and promotion in older adults are restricted by models and approaches of care (Berg et al, 2005;Resnick, 2003a), inefficiencies in procedures and processes (Resnick, 2003a), inadequate numbers of staff (Toofany, 2008), and nurses who are considering care and services only from the medical perspective (Berg et al, 2005). The results of the current study are consistent with the literature.…”
Section: Discussionsupporting
confidence: 93%
“…It is also affected by individual factors such as their health care providers' beliefs and attitudes (Lin et al, 2011;Resnick, 2003a), encouragement by health care staff (Sims, Kerse, Naccarella, & Long, 2000), special motivation requirements (Resnick, 2003a), accessibility of resources (Gallant & Dorn, 2001;Tishler, McCarthy, Rind, & Hamel, 2000), their number of chronic illnesses, and their mental, physical, and cognitive states (Gallant & Dorn, 2001;Resnick, 2003a;Resnick & Spellbring, 2000). In addition to individual factors, other factors that influence older adults' participation in health-promoting activities include models and approaches to care (Berg, Hedelin, & Sarvimäki, 2005;Resnick, 2003b), health expenses (Lucas, Orshan, & Cook, 2000), deficiencies in procedures and processes (Resnick, 2003a), shortages of staff and social exclusion (Toofany, 2008), and nurses' consideration of care and practices from solely the medical perspective (Berg et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Medicine implies complementary and alternative medicine, while holistic nursing means to view all a patients' aspects in the present situation [7,8]. In their study from 1987 Goldstein et al investigated differences between Holistic Physicians (HP) (members of the American Holistic Medical Association) and Family Physicians (FP).…”
Section: Introductionmentioning
confidence: 99%
“…Interviews of integrative medical doctors conducted by Willis and Rayner (7) and with nurses by Berg,Hedelin (20) found that these practitioners endeavoured to take a holistic view but felt somewhat constrained by the bio-medical framework of their practice. Treatment was primarily focused on managing involved components rather than treating the components in a deep interrelated way to regain inner health and well-being (7,20,21).…”
Section: Integration and Implementationmentioning
confidence: 99%